The effectiveness of Assistance for Child Protection Institutions Against Priority Program Achievements Child Protection in North Lombok - Aswadi, Khairul; Rauzi, Fathur; Kamil, M. Ikhsan (LEGAL BRIEF, 2023)
The issue of children's rights recently has been phenomenal, ranging from kidnapping, trafficking, to economic and sexual exploitation of children. This research uses a qualitative approach. In this case, qualitative methodology is used by researchers as a research tool to design studies, collect and analyze data. This approach is used to answer questions and describe the effectiveness of support from NTB Child Protection Institutions on the Achievements of Priority Child Protection Programs in North Lombok Regency. The object of research in this research is the Regional Government of North Lombok Regency, the departments in charge of children's problems, or the departments that have the authority to make policies related to children's problems. The results of this study and research show that in general Gawe Gubuk has very good work effectiveness and efficiency, because the complexity of the problems experienced by one child with high vulnerability can be resolved in a short time, cheaply and cuts down the long bureaucracy between one OPD service and other. Obstacles faced by the NTB Child Protection Agency in efforts to implement child protection through the "Gawe Gubuk" program include the gap or gap in community capacity to respond to the complexity of children's vulnerability issues, the service integration mindset has not been institutionalized, the limited number and quality of professional service human resources